2022
DOI: 10.3390/ijms232315165
|View full text |Cite
|
Sign up to set email alerts
|

CD200 as a Potential New Player in Inflammation during Rotator Cuff Tendon Injury/Repair: An In Vitro Model

Abstract: Rotator cuff tendon (RCT) disease results from multifactorial mechanisms, in which inflammation plays a key role. Pro-inflammatory cytokines and tendon stem cell/progenitor cells (TSPCs) have been shown to participate in the inflammatory response. However, the underlying molecular mechanism is still not clear. In this study, flow cytometry analyses of different subpopulations of RCT-derived TSPCs demonstrate that after three days of administration, TNFα alone or in combination with IFNγ significantly decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Activated TDSCs improve the inflammatory response in tendon tissue, increase the secretion of IL10, inhibit the polarization of macrophages towards M1 ( Tarafder et al, 2017 ), and promote the M2 polarization of macrophages ( Mao et al, 2022 ). Annexin A1 and CD200 serves as an important marker and drug target in tendon inflammatory diseases ( Liu et al, 2018 ; Giancola et al, 2022 ). Excessive inflammation may induce senescence in TDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Activated TDSCs improve the inflammatory response in tendon tissue, increase the secretion of IL10, inhibit the polarization of macrophages towards M1 ( Tarafder et al, 2017 ), and promote the M2 polarization of macrophages ( Mao et al, 2022 ). Annexin A1 and CD200 serves as an important marker and drug target in tendon inflammatory diseases ( Liu et al, 2018 ; Giancola et al, 2022 ). Excessive inflammation may induce senescence in TDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Tenocytes cultures were maintained in CO 2 stove at 37 °C until reach total cellular confluence. As there are currently no protocols utilizing conditioned medium from tendon cells, the authors chose to use confluent cultures to produce the conditioned medium based on established protocols from previous tendon cell culture studies, that cultivated those cells until confluence (15,18,19). Besides that, previous analyses described that muscle and tendon-derived cells achieved higher cell numbers and full confluence more rapidly (20).…”
Section: Tenocyte Primary Cell Cultures and Preparation Of Conditione...mentioning
confidence: 99%
“…The mean age of patients with rotator cuff tear was 60 years (53-71) -the mean tear size was 2.9 cm 2 . The mean age of the healthy tendon control group was 26 years (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Patient Demographicsmentioning
confidence: 99%
“…For, example, Stolk et al 2017 demonstrated that tenocytes in vitro responded to inflammatory environments with altered surface marker and cytokine profiles (IL-6, IL-8 and monocyte chemoattractant protein 1), inducing a pro-inflammatory macrophage polarization, 2 characterised by CD 80 expression and a decreased HLA-DR-expression [22]. Another study by Giancola et al 2022 demonstrated the role of tenocytes (tendon stem cell/progenitor cells) in releasing CD 200 ligand which binds to CD 200 receptors located on immune cells such as macrophages resulting in an upregulation of inflammatory processes during tendon injury/repair [23].…”
Section: Introductionmentioning
confidence: 99%